Prevalence and Risk Factors of Vape Use among Adolescents in Indonesia: A Quantitative Approach - Diah Sutha; Eka Wilda Faida; Nathratul Ayeshah Binti Zulkifli; Christine; Siti Novianti; Asri Handayani Solihin; Muhadi (YCAB Publisher, 2026)
Background: The prevalence of electronic cigarette use, or vaping, among Indonesian adolescents has risen sharply, reaching 15.5% in 2023. This phenomenon is driven by a socio-cultural shift where vaping is perceived as a symbol of modernity, yet literature exploring the interplay between cognitive factors and the digital landscape in Indonesia remains limited. Objective: This study aims to analyze the influence of health knowledge, attitudes, peer influence, and product accessibility on vaping behavior among adolescents. Methods: A quantitative study with a cross-sectional design was conducted among 412 adolescents (aged 15–19) across five major regions in Indonesia. Data were collected via an online questionnaire using stratified random sampling. Data analysis involved Chi-square tests and Multivariate Logistic Regression. Results: The results indicate that peer influence is the strongest predictor of vaping (p = 0.000; OR = 4.12), followed by product accessibility (p = 0.004; OR = 2.54) and low health knowledge (p = 0.031; OR = 1.96). Conversely, permissive attitudes did not show a statistically significant relationship with usage (p = 0.084). Conclusion: Adolescent vaping is driven more by social group dynamics and ease of access in the digital environment than by individual attitudes. Policy interventions should focus on digital distribution oversight through Electronic KYC protocols and strengthening parental roles to mitigate peer pressure.